(untitled) (Journal of Hama University, 2024)
The study aimed to explore the level of health awareness among graduated mothers working in kindergartens, to know the level of growth of kindergarten children, and to show the relationship between the level of health awareness of graduated mothers and the level of growth of their children according to the indicators of height, weight and body mass index. The study was limited to married female graduates with a license or/and educational qualification diploma working within the field of kindergartens as teachers or administrators and from the age of 25-38 years. The sample also included children of male and female graduates. The study sample consisted of (483) female teachers and (313) children. After taking the children’s anthropometric measurements (weight, height, and extracting the body mass index) according to the instructions of the World Health Organization, the health awareness scale (prepared by the researcher) was applied to working mothers, and the data was processed using the organization’s (WHO Anthro plus) program and the statistical program StatSoft Statistica. The study concluded that the health awareness on the overall scale was low for graduates of education and arts, while the health awareness of science graduates was acceptable and for health sciences graduates was high. Graduates of the faculties of natural sciences outperformed graduates of the faculties of humanities on the themes of nutrition, infectious diseases, environmental health and personal health, and there were no significant differences on the theme of addiction. In addition, there were no differences between children in weight and body mass index at the age of 4 years, but the differences were significant for body length at the age of 5 years, and also significant when comparing males with females. The differences were not significant between the lower and higher levels of health awareness of the graduated mothers